Semantics of Turkish free conditionals - Akpınar, Kadernur. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
The aim of the present research is to provide a novel compositional semantic analysis for Turkish conditional sentences with wh-phrases in their antecedents (wh conditionals henceforth), which are ambiguous between question and free conditional readings, the latter being the term I use for what roughly corresponds to English sentences with wh-ever phrases. Demirok (2017) is the only existing analysis of free conditionals in Turkish, which builds on Rawlins (2013). I show that Demirok’s and Rawlins’s view, which assumes Hamblin’s (1973) semantics of wh phrases, overgenerates, thus I suggest an alternative to it which assumes Rullman and Beck’s (1998) semantics of wh-phrases as restricted variables, instead. I argue that a wh-phrase can be bound by a universal modal operator, and this results in a free conditional reading, whereas, when it is bound by a question operator (as in Rullman and Beck, 1998), the question reading arises. Lastly, I turn to free conditionals involving an existential modal, and observe that one needs to stipulate the presence of a covert universal modal in them, in order to account for their truth conditions. The proposal in this dissertation contributes a new perspective on wh-conditionals in Turkish and possibly in other languages, which exhibit similar structures.
Keywords: Turkish language -- Semantics.